2009
DOI: 10.2478/s12175-009-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Interval estimation of the mean of a normal distribution based on quantized observations

Abstract: ABSTRACT. We consider the problem of making statistical inference about the mean of a normal distribution based on a random sample of quantized (digitized) observations. This problem arises, for example, in a measurement process with errors drawn from a normal distribution and with a measurement device or process with a known resolution, such as the resolution of an analog-to-digital converter or another digital instrument. In this paper we investigate the effect of quantization on subsequent statistical infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…We conjecture that the unexpected non-monotonic behavior of the posterior for identical data when using the reference prior is due to this inherent difficulty. Some further aspects pointing towards an inherent difficulty of the discrete problem for x (1) = x (n) follow from the work of Witkovsky and Wimmer (2009), who noted that the maximum likelihood estimator for (μ, σ ) does not exist in this case. Furthermore, they stated that the fiducial solution to the discrete problem requires choosing a 'predetermined random mechanism', as a consequence of which it appears that such solution depends on this choice just as a Bayesian inference depends on the choice of prior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We conjecture that the unexpected non-monotonic behavior of the posterior for identical data when using the reference prior is due to this inherent difficulty. Some further aspects pointing towards an inherent difficulty of the discrete problem for x (1) = x (n) follow from the work of Witkovsky and Wimmer (2009), who noted that the maximum likelihood estimator for (μ, σ ) does not exist in this case. Furthermore, they stated that the fiducial solution to the discrete problem requires choosing a 'predetermined random mechanism', as a consequence of which it appears that such solution depends on this choice just as a Bayesian inference depends on the choice of prior.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the continuous problem where the fiducial solution is uniquely defined (and is numerically the same as the Bayesian solution with the standard prior). In fact, Witkovsky and Wimmer (2009) proposed a different 'predetermined random mechanism' than that of Hannig et al (2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the theoretical modelling of the problem Monte Carlo simulation [23][24][25][26][27] has been used. Two significant factors contributing to the measurement outcome and uncertainty are always assumed in [13][14][15][16][17][18][19][20][21][22][23][24][25][26] to be present: finite resolution and Gaussian noise. In the majority of these publications, it is generally concluded that if the sample standard deviation s is sufficiently large in comparison to the resolution or quantization step size q of the measurement instrument (about 0.5 ), s q ≥ the effect of the finite resolution will be insignificant, and conventional statistical inference will be valid.…”
Section: Introductionmentioning
confidence: 99%